RESEARCH OF THE ANTIBACTERIAL EFFECT OF NANO-FILLED POLYMER MATERIALS - ІЩЕНКО, О. В.; ПЛАВАН, В. П.; ШИДЛОВСЬКА, О. А.; ХАРЧЕНКО, Є. (Technologies and Engineering, 2024)
Purpose. The aim of the scientific work is to research the antibacterial effect of nano-filled polymer materials based on a mixture of polypropylene/co-polyamide with the addition of carbon nanotubes. Methodology. To evaluate the antibacterial effect of nano-filled polymer materials, reference strains of Escherichia coli ATCC 25922, Staphylococcus aureus ATCC 25923 and Pseudomonas aeruginosa ATCC 27853 bacteria were used. The antibacterial effect of polymer samples was determined by the method of redox indication using sodium resazurinate. To investigate the ability of bacterial cells to attach to polymeric materials, samples taken after 24-hour cultivation were also analyzed using the sodium resazurinate test. Statistical validity was tested using the Wilcoxon t-test. Findings. The antibacterial effect of nanofilled polymer materials based on a mixture of polypropylene/copolyamide with the addition of carbon nanotubes was studied. It was established that the original polypropylene/co-polyamide with carbon nanotubes reliably inhibits the growth of E. coli. Investigation of anti-adhesive properties of polymers showed effective and reliable repellency against E. coli, P. aeruginosa and S. aureus cell attachment for polypropylene/co-polyamide with carbon nanotubes. Originality The scientific novelty of the work consists in establishing the antibacterial and anti-adhesive properties of nano-filled polymer materials based on a mixture of polypropylene/co-polyamide with the addition of carbon nanotubes. Practical value The antibacterial effect of the original polypropylene/co-polyamide with the addition of carbon nanotubes (1 wt.%) was established, as well as the high anti-adhesive effect of polypropylene/co-polyamide with the addition of carbon nanotubes against a number of bacterial strains, which is important for materials in contact with wound surfaces.